2010
DOI: 10.1177/2040622310380100
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary treatment of systemic lupus erythematosus: an update for clinicians

Abstract: Abstract:The prognosis for patients with systemic lupus erythematosus (SLE) has improved significantly, with 20-year survival now approximately 80% owing partly to effective treatment. SLE treatment has evolved from the use of conventional drugs such as hydroxychloroquine and corticosteroids, nonspecific immunosuppressants including mycophenolate mofetil, to targeting selective components of the immune cascade with a view to increased efficacy, tolerability and safety profile. These novel treatments include B-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
56
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 85 publications
0
56
0
Order By: Relevance
“…The risk for NVD was much higher in SLE patients than in controls and several factors could contribute to this higher risk, including medications to control disease activity or prevent flares, such as antimalarials. These treatments have been reported to have gastrointestinal side effects such as nausea and vomiting . Although antimalarial use was higher in patients with NVD, as other studies have reported in patients with rheumatic diseases, this possible association was not found in the multivariable analysis.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The risk for NVD was much higher in SLE patients than in controls and several factors could contribute to this higher risk, including medications to control disease activity or prevent flares, such as antimalarials. These treatments have been reported to have gastrointestinal side effects such as nausea and vomiting . Although antimalarial use was higher in patients with NVD, as other studies have reported in patients with rheumatic diseases, this possible association was not found in the multivariable analysis.…”
Section: Discussionmentioning
confidence: 59%
“…These treatments have been reported to have gastrointestinal side effects such as nausea and vomiting. 20 Although antimalarial use was higher in patients with NVD, as other studies have reported in patients with rheumatic diseases, 21 this possible association was not found in the multivariable analysis. Notably, the controls included in this study also had a high prevalence of FGIDs (54.1%), which was similar to that reported in the Mexican population (58.4%).…”
Section: Discussionmentioning
confidence: 73%
“…Corticosteroids have a central role in the treatment of SLE . According to one study, up to 80% of SLE patients are treated with corticosteroids during the course of their disease, most of them for long periods .…”
Section: Discussionmentioning
confidence: 99%
“…37 Corticosteroids have a central role in the treatment of SLE. 38 According to one study, up to 80% of SLE patients are treated with corticosteroids during the course of their disease, most of them for long periods. 39 Earlier reports ascribed dementia to steroid treatment, and subsequent cognitive improvement was observed following their cessation.…”
Section: Discussionmentioning
confidence: 99%
“…The patient's prognosis with the SLE or SLE is known to be considerably improved with 20 years of survival now roughly about 80% partly owing to the treatments which are effective [10]. SLE is thought to be a "multisystem autoimmune disease" that tends to impact different organs as well as tissue in an individual's body ultimately causing dysfunction and damage.…”
Section: Discussionmentioning
confidence: 99%